2008
DOI: 10.1089/cbr.2007.0444
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Binding, Biodistribution, and Metabolism Studies of64Cu-DOTA-Cetuximab, a PET-Imaging Agent for Epidermal Growth-Factor Receptor-Positive Tumors

Abstract: The epidermal growth-factor receptor (EGFR) and its ligands have been recognized as critical factors in the pathophysiology of tumorigenesis. Overexpression of the EGFR plays a significant role in the tumor progression of a wide variety of solid human cancers. Therefore, the EGFR represents an attractive target for the design of novel diagnostic and therapeutic agents for cancer. Cetuximab (C225, Erbitux) was the first monoclonal antibody targeted against the ligand-binding site of EGFR approved by the Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…The CB-TE1A1P:cetuximab ratio was 1.5 for CB-TE1A1P–cetuximab synthesized via NHS-aided reactions, compared to 5 chelators/mAb for previously reported DOTA–cetuximab. 10 The low ratio of the chelator to antibody is likely responsible for the lower SA of 64 Cu-CB-TE1A1P–cetuximab compared to the DOTA and CB-TE1K1P-PEG 4 -DBCO conjugates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CB-TE1A1P:cetuximab ratio was 1.5 for CB-TE1A1P–cetuximab synthesized via NHS-aided reactions, compared to 5 chelators/mAb for previously reported DOTA–cetuximab. 10 The low ratio of the chelator to antibody is likely responsible for the lower SA of 64 Cu-CB-TE1A1P–cetuximab compared to the DOTA and CB-TE1K1P-PEG 4 -DBCO conjugates.…”
Section: Resultsmentioning
confidence: 99%
“…10 Copper-64-labeled cetuximab (∼0.74 MBq, 1.0–6.0 μg in 150 μL) was injected via tail vein into HCT116 tumor-bearing mice (7–9 weeks). At 24 and 48 h after injection, mice were sacrificed and selected organs were removed, weighed, and counted on a γ counter (Beckman 8000; Irvine, CA).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For therapy, lutetium-177 (Jalilian et al, 2016) and yttrium-90 (Niu et al, 2010) have been used. Ping et al (2008) reported a preclinical study related to the use of cetuximab as a PET agent, directed to tumors overexpression` EGFR. Cetuximab was conjugated with DOTA chelator (1,4,7,10 -tetraazacyclododecane tetraacetic acid), for radiolabeling with copper-64 (T 1/2 = 12.7 hours).…”
Section: Introductionmentioning
confidence: 99%